Novel nanofabrication process of oxide patterns using AFM in low operating temperature: a promising lithographic tool for future molecular electronics - Sutjipto, Agus Geter Edy; -, Afzeri; Muhida, Riza; Mridha, Shahjahan (2007)
Field-induced oxidation has become a promising process that is capable of directly producing high-resolution surface oxide patterns on variety materials. In this report, a low temperature operation of an atomic force microscope (AFM) was used to condense ambient humidity to perform a thin frozen water layer covering a silicon wafer surface. A scanning probe was contacted with the layer and a zero bias voltage was applied to the probe tip. The frozen water film acted both as an electrolyte for forming the oxides and as a resource of hydroxide. Using this technique, a consistency in height of about 6 nm silicon dioxide patterns layer could be achieved.